1999
DOI: 10.1126/science.285.5428.732
|View full text |Cite
|
Sign up to set email alerts
|

Host Defense Mechanisms Triggered by Microbial Lipoproteins Through Toll-Like Receptors

Abstract: The generation of cell-mediated immunity against many infectious pathogens involves the production of interleukin-12 (IL-12), a key signal of the innate immune system. Yet, for many pathogens, the molecules that induce IL-12 production by macrophages and the mechanisms by which they do so remain undefined. Here it is shown that microbial lipoproteins are potent stimulators of IL-12 production by human macrophages, and that induction is mediated by Toll-like receptors (TLRs). Several lipoproteins stimulated TLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
1,060
2
16

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,490 publications
(1,119 citation statements)
references
References 40 publications
(29 reference statements)
41
1,060
2
16
Order By: Relevance
“…Our results confirmed that, similar to other bacterial lipoproteins tested in vitro [10,43,44], AaPAL-induced pro-inflammatory cytokine production by mouse macrophages is mediated by TLR2. The PAL of E. coli has also been shown to induce IL-6 and TNF-α production by mouse macrophages via TLR2 in vivo , as demonstrated by using a TLR2 knockout mouse model [22].…”
Section: Discussionsupporting
confidence: 89%
“…Our results confirmed that, similar to other bacterial lipoproteins tested in vitro [10,43,44], AaPAL-induced pro-inflammatory cytokine production by mouse macrophages is mediated by TLR2. The PAL of E. coli has also been shown to induce IL-6 and TNF-α production by mouse macrophages via TLR2 in vivo , as demonstrated by using a TLR2 knockout mouse model [22].…”
Section: Discussionsupporting
confidence: 89%
“…43,70 While initial in vitro studies showed that cellular recognition of lipoproteins from a variety of microorganisms including Mycobacteria, Mycoplasma sp. and the spirochetes Treponema pallidum and B. burgdorferi is mediated by TLR2, 35,36,71 more recent work has revealed a functional interaction between TLR2 and TLR1 that enhances cellular signaling in response to B. burgdorferi lipoprotein OspA. 43 Macrophages from both TLR1-or TLR2-deficient mice incubated with OspA exhibit impaired cytokine and nitric oxide (NO) production compared to wild-type controls.…”
Section: Spirochetal Infectionmentioning
confidence: 99%
“…[17][18][19][20][21] In addition to their critical roles in innate immunity, TLRs are essential in the orientation of the adaptive immune response through the induction of the Th 1 immune response. 22 Among the 10 human TLRs, TLR2 plays a key role in the immune responsiveness to peptidoglycans, 23,24 to lipoteichoic acid of Gram-positive bacteria, 25 to mycobacterial lipoproteins 26 and to leptospiral lipopolysaccharide (LPS). 27 That TLR2-deficient mice are highly susceptible to M. tuberculosis infection 28,29 suggests that mutations that affect TLR2 expression may impair host response to this pathogen.…”
Section: Introductionmentioning
confidence: 99%